2011
DOI: 10.1007/s10342-010-0477-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relascope and fixed-radius plots for the estimation of forest stand variables in northeast Spain: an inventory simulation approach

Abstract: The Bitterlich relascope is a multiple use dendrometer widely used in forest inventory. Although it is most commonly used to estimate basal area, the relascope can also estimate other stand variables, including density and diameter distribution. However, forest stand inventories in Spain rarely use relascope plots to estimate these variables due to the belief that they lead to higher errors than fixed-radius plots due to the heterogeneity of many Mediterranean forests. This study compared the accuracy of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…Ultimately, the transect method was selected as the optimal sampling method in the Arasbaran forests. Pique et al (2011) compared the accuracy of the estimated means of three main stand variables (basal area, stand density, and diameter class distribution) in forest stand inventories performed with relascope plots and with conventional fixed radius circular plots, both measuring a similar number of trees (15)(16)(17)(18)(19)(20). The results showed that for stands with multiple strata and open structures, the Bitterlich relascope provided a more accurate estimate for basal area than for density, while the reverse occurred for fixed radius plots.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, the transect method was selected as the optimal sampling method in the Arasbaran forests. Pique et al (2011) compared the accuracy of the estimated means of three main stand variables (basal area, stand density, and diameter class distribution) in forest stand inventories performed with relascope plots and with conventional fixed radius circular plots, both measuring a similar number of trees (15)(16)(17)(18)(19)(20). The results showed that for stands with multiple strata and open structures, the Bitterlich relascope provided a more accurate estimate for basal area than for density, while the reverse occurred for fixed radius plots.…”
Section: Introductionmentioning
confidence: 99%
“…Forest inventories are usually based on the measurement of some field plots (e.g. one plot per hectare of forest) either of fixed size or using the angle count sampling technique [Gasparini and Di Cosmo, 2015;Piqué et al, 2011], and to average the values measured over stands having uniform structural characteristics [Gregoire and Valentine, 2008]. As usual for the surveys based on statistical sampling, which are preferred for large scale inventories to reduce the fieldwork, the spatial detail is not preserved, which can be problematic especially in forests managed with selective lodging, and characterized by the presence of mixed tree species.…”
Section: Introductionmentioning
confidence: 99%
“…These are based on geometric principles and give values consistent to those obtained by the measurement of trees in standard inventory plots (e.g. Grosenbaugh, 1952;Piqué et al, 2011). …”
Section: Quantification Of Forest Carbon Services In Oak-pine Forestsmentioning
confidence: 80%
“…Palley and Horwitz 1961;Grenier et al, 1991;Piqué et al, 2011). Generating information for basal area and tree density through these alternative methods will be faster, cheaper and easier than using full forest inventories in which the dimensions of all the trees in sampling plots are measured individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation